2001
DOI: 10.1556/004.49.2001.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding intensity on corporeal development, body composition and sexual maturity in female rabbits

Abstract: Twenty-six 6-week old female New Zealand White rabbits were divided into two groups: ad libitum (AL) and 70% restricted (RS) feeding. At the beginning of the experiment the liveweights were practically the same: 0.99 +/- 0.08 vs. 1.01 +/- 0.08 kg in group AL and RS, respectively. At 18 weeks of age the body weight of Group RS rabbits was 84.7% (3.14 +/- 0.24 kg) of the group AL (3.71 +/- 0.31 kg). The apparent digestibility of crude protein was significantly (p < 0.001) higher in Group RS than in Group AL (76.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
11
1
1
Order By: Relevance
“…An increase in protein digestion was often observed in growing rabbits (Xiccato et al, 1992;Gidenne and Feugier, 2009) and adults (Lebas, 1979;Xiccato and Cinetto, 1988;Fodor et al, 2001). Similarly, in these studies the authors found in R animals a better digestive efficiency for energy, but few improvements in lipid or fibre digestion.…”
Section: Effect Of a Post-weaning Feed Restriction On Digestion And Dmentioning
confidence: 75%
“…An increase in protein digestion was often observed in growing rabbits (Xiccato et al, 1992;Gidenne and Feugier, 2009) and adults (Lebas, 1979;Xiccato and Cinetto, 1988;Fodor et al, 2001). Similarly, in these studies the authors found in R animals a better digestive efficiency for energy, but few improvements in lipid or fibre digestion.…”
Section: Effect Of a Post-weaning Feed Restriction On Digestion And Dmentioning
confidence: 75%
“…In the late-maturing 24-week-old Hungarian Giant rabbits the corresponding figures were 89.7% for body weight and 87.5% for average body weight gain. In the New Zealand White breed, restricted feeding delayed sexual maturity with later starting ovarian activity, weaker ovarian responsiveness, and a smaller number of tertiary follicles on the ovarian surface (Fodor et al, 2001a). This shows that the degree of optimal feed restriction considerably depends on the genotype in female rabbits.…”
mentioning
confidence: 99%
“…One of the most important objectives of the prospective development is to achieve sexual maturity at an optimum age. The growth of organs at a different rate that depends on feeding (nutritional allometry) is currently known in heifers, dogs and cats (Rivers and Burger, 1989) and in different rabbit breeds such as the 'Pannon' White, Danish White and crossbred varieties (Kenessey et al, 1998) as well as the New Zealand White and Hungarian Giant female rabbits (Fodor et al, 2000(Fodor et al, , 2001b. Fekete and Gippert (1981) studied the effects of different levels of feed restriction in broiler rabbits.…”
mentioning
confidence: 99%
See 2 more Smart Citations